Balancing charge in the complementarity-determining regions of humanized mAbs without affecting pI reduces non-specific binding and improves the pharmacokinetics - Datta-Mannan, Amita; Thangaraju, Arunkumar; Leung, Donmienne; Tang, Ying; Witcher, Derrick R; Lu, Jirong; Wroblewski, Victor J (mAbs, 2015)
Lowering the isoelectric point (pI) through engineering the variable region or framework of an IgG can improve its exposure and half-life via a reduction in clearance mediated through non-specific interactions. As such, net charge is a potentially important property to consider in developing therapeutic IgG molecules having favorable pharmaceutical characteristics. Frequently, it may not be possible to shift the pI of monoclonal antibodies (mAbs) dramatically without the introduction of other liabilities such as increased off-target interactions or reduced on-target binding properties. In this report, we explored the influence of more subtle modifications of molecular charge on the in vivo properties of an IgG1 and IgG4 monoclonal antibody. Molecular surface modeling was used to direct residue substitutions in the complementarity-determining regions (CDRs) to disrupt positive charge patch regions, resulting in a reduction in net positive charge without affecting the overall pI of the mAbs. The effect of balancing the net positive charge on non-specific binding was more significant for the IgG4 versus the IgG1 molecule that we examined. This differential effect was connected to the degree of influence on cellular degradation in vitro and in vivo clearance, distribution and metabolism in mice. In the more extreme case of the IgG4, balancing the charge yielded an ∼7-fold improvement in peripheral exposure, as well as significantly reduced tissue catabolism and subsequent excretion of proteolyzed products in urine. Balancing charge on the IgG1 molecule had a more subtle influence on non-specific binding and yielded only a modest alteration in clearance, distribution and elimination. These results suggest that balancing CDR charge without affecting the pI can lead to improved mAb pharmacokinetics, the magnitude of which is likely dependent on the relative influence of charge imbalance and other factors affecting the molecule's disposition.